Pengembangan Aplikasi Pasubarea (Patani Subang Makmur Jeung Maju) Berbasis Website Berisi Informasi Terpadu Untuk Mendukung Usaha Tani - Erfan Handoko; Ida Hidayat; Udayat; Evi Rahayu; Acep Imam Hidayat; Asep Hambali; Edah Adijah; Iwan Setiawan; Nining Ratnaningsih; Pipiet Sumanti; Andri; Sutisna Sanjaya; Retno Widawati (PT. Mitra Jurnal Indonesia, 2023)
Abstract Indonesia is a fertile country because the area is located in the tropics and is crossed by a series of volcanoes. Tropical climate conditions allow Indonesia to have types of vegetation that can survive for agricultural cultivation. Based on data obtained from the Central Statistics Agency (BPS), West Java Province is in third place. A total of 5.2 million tons of rice is produced from this region. The area of agricultural rice fields constitutes 26 percent of the total area of West Java. Of the various cities and regencies in the West Java region, Subang Regency is in third place with the largest area of agricultural land. However, farmers in Subang still experience various difficulties, such as, (1) Farmers are always at a disadvantage when commodity prices fall; (2) Farmers still use the